Education Focussed on Waste With the Aim of Protecting the Environment - FESZTEROVÁ, MELÁNIA (Journal of Education, Technology and Computer Science, 2018)
Environmental education is the key component of tool, for the preservation of the environ-ment, which can increase knowledge. Dissemination and increasing of knowledge is leading to improved attitudes to environment. Attitudes are changing behaviour of people. Environmental education is frequently undertaken as a conservation intervention designed to change the attitudes and behaviour of recipients. Much conservation education is aimed at children and students, with the rationale that they might influence the attitudes of their parents, who will consequently change their behaviour. Our paper provides the first strong support for the suggestion that environmental education can be transferred between generations and indirectly induce targeted behavioural changes.The aim of the paper is to inform pupils, students, teachers and future teachers with on-line innovative study materials contained in the e-learning course prepared under the KEGA Project (Cultural and Educational Grant Agency) No. 044UKF-4/2017. This project describes treatment of the surrounding environment and countryside and suggests a way to prevent it. The training topics of the course analyse the situation, look for solutions and the basics to improve the current state of the environment. The course focuses on the chemical nature of waste and waste management from the point of view of educational work and its application in practice